Effect of Aerobic Exercise Program on Premenstrual Syndrome in Women of Hot and Cold Temperaments - F Jafarnejad (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2016)
BACKGROUND AND OBJECTIVE: Premenstrual syndrome is one of the most common disorders in women of childbearing age, which is accompanied by periodic changes in physical, mental and behavioral condition. Exercise is one of the proposed therapies to reduce the symptoms of this syndrome. Based on principles of Traditional Persian medicine (PM), type and intensity of symptoms and effectiveness of exercise depend on patient's "temperament" (called “Mizaj” in Persian medicine). This study was carried out to determine the effect of aerobic exercise program on premenstrual syndrome in women of hot and cold temperaments.